Active steering wheel shimmy control for electric vehicle by sampled-data output feedback. (January 2019) - Meng, Qinghua; Qian, Chunjiang; Shu, Yong
Abstract: In this paper, a new two Degree of Freedom (DOF) shimmy dynamic model of an Electric Vehicle (EV) with independent suspension subject to uncertain disturbances is built via Lagrange's theorem firstly. Secondly, Based on the built model, an active control method is proposed to solve the shimmy problem of the steering system via a sampled-data output feedback controller. The output feedback domination approach is also used to dominate uncertain disturbances by using a scaling gain. With the help of these tools, the sampling period and scaling gain are calculated to guarantee global stability and disturbance attenuation for the closed-loop control system. Finally, simulations and tests are conducted to verify the effectiveness of the sampled-data output feedback controller for the EV's shimmy problem under different conditions. Highlights: A shimmy model of an EV considering external disturbances is presented. A linear state estimate discrete-time observer is designed for the system. A shimmy active controller via a scaling gain is designed to dominate disturbance.